Risk of sarcopenia in women with breast cancer: a comparative analysis of screening tools - Vanusa Felicio de Souza Mamede; Rayne de Almeida Marques Bernabé; Thalita Gonçalves Santos; Larissa Leopoldino da Silva; Mariana de Souza Vieira; José Luiz Marques-Rocha; Valdete Regina Guandalini (BMC Cancer)
Abstract Background Sarcopenia is characterized by the loss of muscle strength and mass and is associated with poorer clinical outcomes in women with breast cancer. However, no specific tool is capable of assessing the risk of sarcopenia in this population. Therefore, the aim of the present study was to compare the performance of SARC-F, SARC-CalF, and BMI-adjusted SARC-CalF as screening tools for the risk of sarcopenia in women with breast cancer. Methods An observational cross-sectional study was conducted involving women with breast cancer diagnosed in the previous 12 months. The risk of sarcopenia was identified by SARC-F, SARC-CalF, and BMI-adjusted SARC-CalF. As proposed by the EWGSOP2, sarcopenia was defined as low muscle strength (grip strength: <23.0 kg) and appendicular skeletal muscle mass index < 6.38 kg/m2 (determined by dual-energy X-ray absorptiometry). The performance of the screening tools was assessed by calculating specificity, sensitivity, positive and negative predictive values, and area under the ROC curve (AUC). AUC values were compared using DeLong’s test. Results This study included 168 women with a mean age of 54.8 ± 11.3 years. The prevalence of sarcopenia risk ranged from 10.1 to 36.6%, depending on the screening tool employed. The prevalence of sarcopenia was 8.3%. Using the presence of sarcopenia as reference, the SARC-F had an AUC of 0.550 [(0.396–0.703) p = 0.54], sensitivity of 21.4%, and specificity of 85.7%; the SARC-CalF had an AUC of 0.790 [(0.654–0.927) p < 0.001], sensitivity of 42.8%, and specificity of 92.2%; the BMI-adjusted SARC-CalF had an AUC of 0.521 [(0.385–0.658) p = 0.08], sensitivity of 28.6%, and specificity of 63.0%. Therefore, the SARC-CalF tool had low sensitivity and high specificity. Conclusion SARC-CalF performed the best compared to the alternatives provided. However, based on the current results, it may be necessary to reconsider the use of either of these instruments as a screening option for sarcopenia risk in women with breast cancer.